Do Households Where Women Own Land Fare Better for Food Security? Evidence for Tanzania - Sara Burrone; Gianna Claudia Giannelli (Institute of Labor Economics (IZA), 2023)
This paper aims to study the relationship between women's land ownership and household food security in Tanzania, using data from three waves of the Tanzanian National Panel Survey. The analysis focuses on the Household Dietary Diversity Scale (HDDS) as a measure of food security, and we categorize land ownership by gender and whether it is solely or jointly owned. Additionally, we examine the impact of the gendered division of crop cultivation on household food security, distinguishing between cash crops and food crops. We estimate several fixed-effects specifications and perform a heterogeneity analysis to disentangle the effects of women's land ownership across households with varying levels of dependence on home-produced food. The findings reveal that women's land ownership significantly influences household dietary diversity. Specifically, women's sole ownership of food crops and joint ownership of cash crops have positive effects on household food security, especially for households reliant on purchased food. These results underscore the importance of women's ownership of income-generating crops in enhancing food security. Overall, this research provides valuable insights for policymakers, emphasizing the significance of women's land ownership in driving household food security in Tanzania. By uncovering the positive impacts of women's land ownership, the study highlights the importance of gender equity in agricultural systems and the potential for women's empowerment to foster sustainable development and food security.
Keywords: O12; Q15; 330; gender equity; food security; land ownership; Tanzania